2021
DOI: 10.7717/peerj.11194
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation potential of PGPR to protect tomato against Fusarium wilt and promote plant growth

Abstract: Soilborne fungal diseases are most common among vegetable crops and have major implications for crop yield and productivity. Eco-friendly sustainable agriculture practices that can overcome biotic and abiotic stresses are of prime importance. In this study, we evaluated the ability of plant growth-promoting rhizobacterium (PGPR) Bacillus aryabhattai strain SRB02 to control the effects of tomato wilt disease caused by Fusarium oxysporum f. sp. lycopersici (strain KACC40032) and promote plant growth. In vitro bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…The systemic acquired resistance (SAR) is an SA-dependent response, also known as a long-distance signaling mechanism that provides a broad-spectrum and long-lasting resistance to secondary infections across the plant [ 10 , 30 ]. Therefore, we analyzed whether the AtbZIP62 TF could have contributed to SAR in response to Pst DC3000 avrB .…”
Section: Resultsmentioning
confidence: 99%
“…The systemic acquired resistance (SAR) is an SA-dependent response, also known as a long-distance signaling mechanism that provides a broad-spectrum and long-lasting resistance to secondary infections across the plant [ 10 , 30 ]. Therefore, we analyzed whether the AtbZIP62 TF could have contributed to SAR in response to Pst DC3000 avrB .…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Bacillus aryabhattai SRB02 significantly inhibited tomato wilt disease caused by F. oxysporum f. sp. lycopersici and promoted plant growth by modulating endogenous hormones (SA, JA) [ 15 ]. Dimopoulou et al [ 137 ] revealed that tomato defence signalling pathways depended on the dose of application.…”
Section: Mechanisms Of Biological Controlmentioning
confidence: 99%
“…Several Bacillus spp. have been proven to be promising biocontrol agents for controlling tomato pathogens, both in laboratory and field conditions [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PGPR, as microbial inoculants, have a positive impact on soil biology and it can be recognized as a good strategy for recovering semiarid areas and degraded ecosystems [28]. PGPR and their attributes with plants are well known and starting to be exploited commercially in many crops [29,30].…”
Section: Introductionmentioning
confidence: 99%